Collaborative Ad-hoc Multimedia Authoring via Mobile Devices - Uscamayta, A. Omar M.; Cunha, Bruna C. R.; Martins, Diogo S.; Pimentel, Maria G. C. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2017: Proceedings of the 23rd Brazilian Symposium on Multimedia and the Web, 2017)
A particularly challenging situation in amateur multimedia authoring is ad-hoc collaborative capture, i.e., a process that, having no pre-production phase, demands live coordination between multiple authors. Important problems to realize such scenarios include proper synchronization of media elements by multiple devices, and which information to include in the resulting collaboratively authored multimedia document. In this paper, we report how our collaborative authoring system tackles these ad-hoc multimedia capture problems by combining mobile and web applications. We present a case study in the educational domain and discuss the results of a user study